2003
DOI: 10.1046/j.1365-2486.2003.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Controls on microbial CO2 production: a comparison of surface and subsurface soil horizons

Abstract: Although a significant amount of the organic C stored in soil resides in subsurface horizons, the dynamics of subsurface C stores are not well understood. The objective of this study was to determine if changes in soil moisture, temperature, and nutrient levels have similar effects on the mineralization of surface (0–25 cm) and subsurface (below 25 cm) C stores. Samples were collected from a 2 m deep unsaturated mollisol profile located near Santa Barbara, CA, USA. In a series of experiments, we measured the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
227
7
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(261 citation statements)
references
References 49 publications
25
227
7
2
Order By: Relevance
“…This ratio did not vary significantly with depth (e.g., the average for 0-15 cm depth was 3.9 and for > 15 cm depth was 4.1) and was not correlated with total whole soil OC content or the OC content of either fraction. Although Fierer et al (2003) found that surface soil exhibited greater sensitivity of mineralization to drought (potentials of -1 and -5 MPa), their results may not be comparable with the results obtained in this study for several reasons. The corresponding water contents were much drier than those used in this study.…”
Section: Water Content and Depthcontrasting
confidence: 96%
See 3 more Smart Citations
“…This ratio did not vary significantly with depth (e.g., the average for 0-15 cm depth was 3.9 and for > 15 cm depth was 4.1) and was not correlated with total whole soil OC content or the OC content of either fraction. Although Fierer et al (2003) found that surface soil exhibited greater sensitivity of mineralization to drought (potentials of -1 and -5 MPa), their results may not be comparable with the results obtained in this study for several reasons. The corresponding water contents were much drier than those used in this study.…”
Section: Water Content and Depthcontrasting
confidence: 96%
“…Although soil temperature and water content change with depth, there is little information on whether the sensitivity of mineralization rates to these variables changes with depth in the profile. Fierer et al (2003) observed that the relation between OC mineralization rates and water potential did not change appreciably with soil depth, although mineralization in surface soils (0-25 cm) was more affected by drought (water potentials of -1.5 to -5.0 MPa) than deeper soils. Mineralization rates at lower depths (25-200 cm) were particularly susceptible to increases in temperature or nutrient availability, possibly due to differences in OC chemical structure and the composition of microbial communities through the profile.…”
Section: Canadian Journal Of Soil Sciencementioning
confidence: 89%
See 2 more Smart Citations
“…Microbial activity may be reduced by suboptimal environmental conditions, nutrient limitation or energy scarcity, and organic matter may be less accessible because of its sparse density or association with reactive mineral surfaces. Microbial biomass decreases with soil depth 58 , and community composition changes to reflect an increase in substrate specialization 59 . Recent studies suggest that energy limitation, or the converse-'priming' (see below) by root exudates or dissolved organic carbon-is an important factor in the subsurface 48,49 .…”
Section: Deep Soil Carbonmentioning
confidence: 99%